(untitled) (Journal of Parents and Teachers, 2023)
Educational development suffer a major shift with the emergence of Gardner’s multiple intelligences, leading to major adaptations and differentiating between learning and understanding. The article reflects on this, adding a new intelligence to the seven already created by Gardner. Little by little this theory is reaching the classroom, but there is still some work to be done.